Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Bibit Tanaman Hutan dan Buah-Buahan Di CV. Agro Utama Mandiri Lestari Kediri - Sendy Mahendra Fatkhi (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2023)
Indonesia, with its vast land and tropical climate, provides abundant resources for agricultural business development, including fruit cultivation. One such example is CV. Agro Utama Mandiri Lestari, situated in Dusun Munengan, Desa Mangunrejo, Kecamatan Ngadiluwih, Kabupaten Kediri, East Java Province. The company specializes in trading fruit and forestry plant seeds. Currently, it is focusing on increasing sales revenue through the implementation of effective marketing strategies. CV. Agro Utama Mandiri Lestari has adopted a marketing strategy involving collaboration with educational institutions and relevant organizations. This approach includes providing educational services in the form of fruit and forestry plant seedling training. The research methodology employed in this study is qualitative, with data collected through observation and interviews. Based on the findings and analysis, it is concluded that CV. PT. Agro Utama Mandiri Lestari implements a marketing strategy involving the four elements of the marketing mix (4P): Product, Price, Place, and Promotion. Various channels such as electronic radio media, pamphlets, training, and seminars are utilized for promotion. This strategy also encompasses different approaches, including seed quality assurance and collaboration with various educational and governmental institutions. The results of this strategy demonstrate a significant increase in sales, thereby positively impacting the development of CV. Agro Utama Mandiri Lestari's business in the agricultural sector.